Application of mathematical modelling to alginate chitosan polyelectrolyte complexes for the prediction of system behavior with Venlafaxine HCl as a model charged drug - Howida K. Ibrahim; Rania Mohamed Hassan Sorour; Ibtehal Salah Ad-din (Elsevier, 2022)
Purpose: This work aimed to develop and analyze the performance of chitosan/alginate polyelectrolyte complex (PEC). Multiple regression and Lab fit curve fitting were applied to derive empirical models for the prediction of zeta potential of plain systems as a function of alginate chitosan ratio. Venlafaxine-HCl was loaded as a model charged drug and empirical models for prediction of its release as a function of time were also derived. Methods: Coacervation method was used for the preparation of green PECs. Preliminary studies were conducted to optimize the preparation method. Pre-adjustment of the pH of alginate and chitosan sols enabled the formation of PECs at alginate/chitosan ratios starting from 1:9 to 9:1. On mixing of alginate and chitosan sols, equal volume dilution method produced spherical particles, while direct mixing method gave fibrous particles. Twenty-seven PECs nanoparticle formulae were prepared using nine alginate/chitosan ratios and three levels of total polymer concentrations. Results: Statistical analysis showed that Zeta potential of the nanoparticle was significantly dependent on alginate/chitosan ratio, while particle size was a function of total polymer concentration. Nine fiber formulae were prepared and evaluated for their appearance and zeta potential. Venlafaxine-HCl release followed anomalous transport mechanism. FT-IR and DSC studies confirmed complexation at the carboxylate and amine site at alginate and chitosan respectively. Conclusion: Chitosan/alginate PECs were successfully obtained without a cross-linker and empirical equations were obtained to help finding the best composition for loading charged drugs and to predict their release profiles.